Algorithm of grey correlation analysis for radar target recognition based on similarity - Rupeng ZHAO; Runlan TIAN; Xuzhou ZHANG; Yibin XIE (Dianxin kexue)
According to the algorithm can't better identify complex radar targets and improve the accuracy while facing parameters overlapping,an algorithm of similarity-grey relational analysis based on similarity was proposed.Firstly,the similarity matrix between the parameters was extracted by the algorithm.And then the grey correlation analysis was used to get the corresponding grey correlation coefficient.At the same time,the weight value was determined according to the matching degree of each parameter,the grey correlation degree of the signal was identified and the library signal was obtained by combining with the grey correlation coefficient,and the target recognition was completed according to the grey correlation degree.Finally,having the grey correlation between the signal and the grey correlation coefficient,which can realize the identification of the complex radar target.The simulation results show that the impact of parame-ters overlapping with high recognition accuracy was reduced,the recognition accuracy was improved,and the identifica-tion of complex system radar targets were quickly realized by the proposed algorithm.